A Post-Occupancy Monitored Evaluation of the Dimmable Lighting, Automated Shading, and Underfloor Air Distribution System in The New York Times Building - Eleanor S. Lee; Luis L. Fernandes; Brian E. Coffey; Andrew McNeil; Robert D. Clear; Thomas L. Webster; Fred S. Bauman; Darryl J. Dickerhoff; David Heinzerling; Tyler Hoyt (Lawrence Berkeley National Laboratory, 2013)
With aggressive goals to reduce national energy use and carbon emissions, the US Department of Energy will be looking to exemplary buildings that have already invested in new approaches to achieving the energy performance goals now needed at a national level. The New York Times Building, in New York, New York, incorporates a number of innovative technologies, systems and processes and could become a model for widespread replication in new and existing buildings. Post-occupancy data are invaluable in establishing confidence in innovation. A year-long monitored study was conducted to verify energy performance, assess occupant comfort and satisfaction with the indoor environment, and evaluate impacts on maintenance and operations. Lessons learned were derived from the analysis; these lessons could help identify and shape policy, financial, or supporting strategies to accelerate diffusion in the commercial building market.